Quantitative Assessment of Variation in CT Parameters on Texture Features: Pilot Study Using a Nonanatomic Phantom - Buch, K.; Li, B.; Qureshi, M.M.; Kuno, H.; Anderson, S.W.; Sakai, O. (American Journal of Neuroradiology, 2017)
SUMMARY: Our aim was to evaluate changes in texture features based on variations in CT parameters on a phantom. Scans were performed with varying milliampere, kilovolt, section thickness, pitch, and acquisition mode. Forty-two texture features were extracted by using an in-house-developed Matlab program. Two-tailed t tests and false-detection analyses were performed with significant differences in texture features based on detector array configurations (Q values = 0.001–0.006), section thickness (Q values = 0.0002–0.001), and acquisition mode (Q values = 0.003–0.006). Variations in milliampere and kilovolt had no significant effect.GLCMgray-level co-occurrence matrixGLGMgray-level gradient matrixGLRLgray-level run lengthMDCTmultidetector row CTRPrun percentage